Project YES! Youth Engaging for Success: A randomized controlled trial assessing the impact of a clinic-based peer mentoring program on viral suppression, adherence and internalized stigma among HIV-positive youth (15-24 years) in Ndola, Zambia - Denison, Julie A.; Burke, Virginia M.; Miti, Sam; Nonyane, Bareng A. S.; Frimpong, Christiana; Merrill, Katherine G.; Abrams, Elizabeth A.; Mwansa, Jonathan K. (PloS one, 2020)
Youth-led strategies remain untested in clinic-based programs to improve viral suppression (VS) and reduce stigma among HIV-positive adolescents and young adults (AYA) in sub-Saharan Africa. In response, Project YES! placed paid HIV-positive youth peer mentors (YPM) in four HIV clinics in Ndola, Zambia including a Children's Hospital (pediatric setting), an adult Hospital and two primary care facilities (adult settings). A randomized controlled trial was conducted from December 2017 to February 2019. Consecutively recruited 15 to 24-year-olds were randomly assigned to an intervention arm with monthly YPM one-on-one and group sessions and optional caregiver support groups, or a usual care comparison arm. Survey data and blood samples were collected at baseline and at the six-month midline. Generalized estimating equation models evaluated the effect of study arm over time on VS, antiretroviral treatment (ART) adherence gap, and internalized stigma. Out of 276 randomized youth, 273 were included in the analysis (Intervention n = 137, Comparison n = 136). VS significantly improved in both arms (I:63.5% to 73.0%; C:63.7% to 71.3.0%) [OR:1.49, 95% CI:1.08, 2.07]. In a stratified analysis intervention (I:37.5% to 70.5%) versus the comparison (C:60.3% to 59.4%) participants from the pediatric clinic experienced a relative increase in the odds of VS by a factor of 4.7 [interaction term OR:4.66, 95% CI:1.84, 11.78]. There was no evidence of a study arm difference in VS among AYA in adult clinics, or in ART adherence gaps across clinics. Internalized stigma significantly reduced by a factor of 0.39 [interaction term OR:0.39, 95% CI:0.21,0.73] in the intervention (50.4% to 25.4%) relative to the comparison arm (45.2% to 39.7%). Project YES! engaged AYA, improving VS in the pediatric clinic and internalized stigma in the pediatric and adult clinics. Further research is needed to understand the intersection of VS and internalized stigma among AYA attending adult HIV clinics. ClinicalTrials.gov NCT04115813.